2013
DOI: 10.1242/jcs.118836
|View full text |Cite
|
Sign up to set email alerts
|

Direct mobilisation of lysosomal Ca2+ triggers complex Ca2+ signals

Abstract: SummaryAccumulating evidence implicates acidic organelles of the endolysosomal system as mobilisable stores of Ca 2+ but their relationship to the better-characterised endoplasmic reticulum (ER) Ca 2+ store remains unclear. Here we show that rapid osmotic permeabilisation of lysosomes evokes prolonged, spatiotemporally complex Ca 2+ signals in primary cultured human fibroblasts. These Ca 2+ signals comprised an initial response that correlated with lysosomal disruption and secondary long-lasting spatially hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
184
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(206 citation statements)
references
References 45 publications
22
184
0
Order By: Relevance
“…Moreover, the reverse was also found to apply; inducing ER Ca 2+ release triggered alkanisation of acidic stores, consistent with lysosomal Ca 2+ release [36]. The ER forms extensive MCSs with lysosomes; 80-100% of lysosomes have been estimated to have an ER MCS [18,27]. It therefore seems likely that ER-lysosome Ca 2+ cross-talk occurs at these MCSs.…”
Section: Er-endocytic Pathway Mcssmentioning
confidence: 64%
See 1 more Smart Citation
“…Moreover, the reverse was also found to apply; inducing ER Ca 2+ release triggered alkanisation of acidic stores, consistent with lysosomal Ca 2+ release [36]. The ER forms extensive MCSs with lysosomes; 80-100% of lysosomes have been estimated to have an ER MCS [18,27]. It therefore seems likely that ER-lysosome Ca 2+ cross-talk occurs at these MCSs.…”
Section: Er-endocytic Pathway Mcssmentioning
confidence: 64%
“…The Ca 2+ mobilizing messenger nicotinic acid adenine dinucleotide phosphate (NAADP) is thought to generate localized Ca 2+ signals that derive from the endocytic pathway and are amplified by ER channels to generate global Ca 2+ signals likely through two-pore channels [25]. Consistent with ER-mediated amplification of lysosomal Ca 2+ signals, it was recently shown that direct release of lysosomal Ca 2+ stores by osmotic permeabilisation is sufficient to initiate subsequent IP3 receptordependent cytosolic Ca 2+ spikes [27]. Moreover, the reverse was also found to apply; inducing ER Ca 2+ release triggered alkanisation of acidic stores, consistent with lysosomal Ca 2+ release [36].…”
Section: Er-endocytic Pathway Mcssmentioning
confidence: 99%
“…According to this hypothesis, channels that allegedly emerged later in evolution (i.e. InsP 3 Rs and RyRs) may serve for signal amplification through consecutive channel activation [90,107,[113][114][115]. In addition, NAADP can also activate Ca 2þ -influx through TPCs localized in the plasmalemma [115], which was confirmed in patch-clamp studies [90].…”
Section: Intracellular Ca 2þ Fluxes and Ca 2þ Regulationmentioning
confidence: 78%
“…In plants, TPCs can be activated by osmotic stress [107] as well as by Ca 2þ ions (this Ca 2þ -dependent activation contributes to regulation of seed germination and stomatal movement [108]). Paramecium, which is another bikont, also seems to possesses TPCs [109].…”
Section: Intracellular Ca 2þ Fluxes and Ca 2þ Regulationmentioning
confidence: 99%
“…Once Ca 2þ -reporter proteins were cloned or engineered (e.g., luminescent aequorin or various fluorescent constructs), this offered more precise control over reporter location by judicious introduction of targeting sequences for a broader array of organelles involved in Ca 2þ signaling, including mitochondria (Rizzuto, Simpson, Brini, & Pozzan, 1992;Suzuki et al, 2014), ER (Suzuki et al 2014), Golgi (Lissandron, Podini, Pizzo, & Pozzan, 2010Pinton, Pozzan, & Rizzuto, 1998), peroxisomes (Drago, Giacomello, Pizzo, & Pozzan, 2008;Lasorsa et al, 2008), and secretory vesicles (Alvarez & Montero, 2002;Dickson, Duman, Moody, Chen, & Hille, 2012;Mitchell et al, 2001;Mitchell et al, 2003;Santodomingo et al, 2008).…”
Section: Null-pointmentioning
confidence: 99%